Examining the moderating role of workload in the relationship between emotional intelligence and caring behavior in healthcare organizations - Chiyem Lucky Nwanzu; Sunday Samson Babalola (International Journal of Business Science & Applied Management (IJBSAM), 2020)
Caring behavior is fundamental in the healthcare setting. This study examined the moderation role of workload in predicting the relationship between emotional intelligence and caring behavior in healthcare organizations. This study is a quantitative, cross-sectional survey, and data was collected through a self-administered questionnaire. The sample comprises 121 healthcare professionals, including medical doctors, nurses, pharmacists, laboratory scientists, and medical records officers in publicly-owned hospitals. The sample size consists of 30% males and 70% of females with a mean age of 41.32 years (SD = 10.25). Results revealed that emotional intelligence has a positive and significant predictive relationship with caring behavior, and that workload has a negative but non-significant interaction effect in the relationship. The findings suggest that emotional intelligence and the volume of work tasks employees are engaged in could have an impact on work outcomes. This knowledge has practical implications for human resource management in terms of recruitment, selection, job assignment, and further training of employees.
Keywords: 650; emotional intelligence; cross-sectional design; workload; affective event theory; healthcare organizations